Genetic Ancestry, Race, and Severity of Acutely Decompensated Cirrhosis in Latin America - Farias, Alberto Queiroz (2023)
BACKGROUND & AIMS: Genetic ancestry or racial differences in health outcomes exist in diseases associated with systemic inflammation (e.g., Covid-19). This study aimed to investigate the association of genetic ancestry and race with acute-onchronic liver failure (ACLF), which is characterized by acute systemic inflammation, multi-organ failure and high risk of short-term death. METHODS: This prospective cohort study analyzed a comprehensive set of data including genetic ancestry and race, among several others, in 1274 patients with acutely decompensated cirrhosis (ADC) who were nonelectively admitted to 44 hospitals from 7 Latin American countries. RESULTS: 395 (31.0%) had ACLF of any grade at enrollment. Patients with ACLF had higher median percentage of Native American genetic ancestry and lower median percentage of European ancestry than patients without ACLF (22.6% vs 12.9% and 53.4% vs 59.6%, respectively). The median percentage of African genetic ancestry was low among patients with ACLF and among those without. In terms of race, a higher percentage of patients with ACLF than patients without ACLF were Native Americans and a lower percentage of patients with ACLF than patients without were European Americans or African Americans. In multivariable analyses that adjusted for differences in sociodemographic and clinical characteristics, the odds ratio for ACLF at enrollment was 1.08 (95% confidence interval [CI], 1.03-1.13) with Native American genetic ancestry and 2.57 (95% CI, 1.84-3.58) for Native American race vs. European American race.